Organic geochemical and paleoenvironmental characterization of the Brown Shale Formation, Kiliran sub-basin, Central Sumatra Basin, Indonesia. (October 2017) - Sefein, Kirellos J.; Nguyen, Thanh X.; Philp, R. Paul
Highlights: Geochemical analysis of a fresh water Tertiary paleolake from rock extracts. B. braunii (A race) was tentatively identified by CSIA and distribution of n -alkanes. 4-Methylsteranes were likely derived from non-marine dinoflagellates. Maximum thermal stress was minimal based on biomarkers, vitrinite, and Tmax data. Some pyrogenic organic matter was observed through PAHs. Abstract: The Central Sumatra Basin (CSB), formed during the Late Eocene (?) to Early Oligocene, is the most prolific hydrocarbon basin in Indonesia. The Brown Shale Formation of the Pematang Group is the sole known source rock for the tens of billions of barrels of oil located in the CSB. Samples analyzed in this study were from the Karbindo coal mine in the Kiliran graben of the Kiliran sub-basin, located on the western side of the CSB. This study incorporates advanced organic geochemical and petrographical data of samples from the Brown Shale Formation, as well as interpretations from previous studies at this location, to construct a detailed paleoenvironment model for this Tertiary lake. The lacustrine source rock was deposited under fresh water conditions, with subtle changes in the environment that resulted in significant changes in ecologies. Based on new data from organic petrography, biomarkers, microscale sealed vessel pyrolysis, and characterization of the polyaromatic hydrocarbons, the organic matter in the Brown Shale Formation was determined to be sourced primarily from lacustrine organisms with a small amount of terrestrial plant input. 4-Methylsterane concentrations and n -alkane distributions indicate that non-marine dinoflagellates and Botryococcus braunii (A race) were likely a significant portion of the local biosphere.